L’évaluation du secteur financier québécois - Robic, Louise (Assurances, 1993)
The province of Québec is responding to the globalization of financial markets by comparing the competitive strengths and weaknesses of its financial sector with those of other Canadian provinces and those of other countries. Legislation is presently under review to improve the efficiency, stability and growth prospects for the entire industry, which includes banks, insurance companies, trusts and brokerage firms. The proposals are divided in three groups designed to strengthen capital standards, harmonize operating guidelines across Canada, and reinforce provincial jurisdiction over inspection and consumer protection.